The Effect of Country of Origin on Brand Image, Perceived Quality, and Purchase Intention of Excavator for Limestone Quarry in East Java Indonesia - Pacanto Prabowo, Prabowo_19 (Archives of Business Research, 2019)
Heavy equipment manufacturers in several countries use a technology to get optimum production. By doing so, they can make the operational cost more efficient. Indonesia, East Java province especially, has geologically abundant non-metallic mineral reserves, one of which is lime stone. Mostly of the consumers who use heavy equipment in the quarry mining industry are looking for the types and heavy equipment suitable for excavated material applications. It also includes perception of the overall quality of a product, to create an image with the value of a brand that can strengthen the effect on purchase intention. This study investigated the effect of the country of origin on brand image, perceived of quality for purchase intention of the hydraulic excavator consumers. This study used the responses of 59 respondents selected based on purposive sampling in a number of regions in East Java province that have non-metallic mineral distribution, namely limestone. The results show that the country of origin has a significant effect on brand image and perceived quality on the purchase intention. In addition to this, it was found that brand image positively and significantly affect the perceived quality and purchase intention. It also provides evidence that manufacture companies from the country of origin should be aware and to set up brand image and perceived quality product to make a brand image. By doing so, the consumers will increase their purchase intention to buy hydraulic excavators, operated at lime stone quarry in East Java province.